Salicylic acid treatment and overexpression of a novel polyamine transporter gene for astaxanthin production in Phaffia rhodozyma - Jia, Jianping; Li, Feifei; Luan, Yifei; Liu, Siru; Chen, Zhitao; Bao, Guoliang (Frontiers in Bioengineering and Biotechnology, 2023)
Phaffia rhodozyma represents an excellent microbial resource for astaxanthin production. However, the yeast's low astaxanthin productivity poses challenges in scaling up industrial production. Although P. rhodozyma originates from plant material, and phytohormones have demonstrated their effectiveness in stimulating microbial production, there has been limited research on the effects and mechanisms of phytohormones on astaxanthin biosynthesis in P. rhodozyma. In this study, the addition of exogenous salicylic acid (SA) at a concentration as low as 0.5 mg/L significantly enhanced biomass, astaxanthin content, and yield by 20.8%, 95.8% and 135.3% in P. rhodozyma, respectively. Moreover, transcriptomic analysis showed that SA had discernible impact on the gene expression profile of P. rhodozyma cells. Differentially expressed genes (DEGs) in P. rhodozyma cells between the SA-treated and SA-free groups were identified. These genes played crucial roles in various aspects of astaxanthin and its competitive metabolites synthesis, material supply, biomolecule metabolite and transportation, anti-stress response, and global signal transductions.This study proposes a regulatory mechanism for astaxanthin synthesis induced by SA, encompassing the perception and transduction of SA signal, transcription factormediated gene expression regulation, and cellular stress responses to SA. Notably, the polyamine transporter gene (PT), identified as an upregulated DEG, was overexpressed in P. rhodozyma to obtain the transformant Prh-PT-006. The biomass, astaxanthin content and yield in this engineered strain could reach 6.6 g/L, 0.35 mg/g DCW and 2.3 mg/L, 24.5%, 143.1% and 199.0% higher than the wild strain at the SA-free condition, respectively. These findings provide valuable insights into potential targets for genetic engineering aimed at achieving high astaxanthin yields, and such advancements hold promise for expediting the industrialization of microbial astaxanthin production.